Giving voice and space to children in health promotion - Kostenius, Catrine (Luleå tekniska universitet, Hälsa och rehabilitering, 2008)
The interest for children's health is a global issue and concerns are voiced in areas of children's psycho-social health and well-being, in many countries including Sweden. There have been a number of research projects undertaken on children's health alerting us of the decrease in children's psycho-social health and well-being, although it seems as if children's perspectives are rare. Therefore the overall aim of this thesis is to describe and develop an understanding of schoolchildren's lived experiences of health and ill health, as well as health promotion activities through children's perspectives. The 128 children who participated were selected from one school district in northern Sweden. The studies included 10 children in a pilot study as well as 99 children age 10-12, all of them attending grades 4-6 in the smallest and largest schools in the school district, one suburban and one rural (I). Twenty- three of these children were invited to an interview (II, III). In addition all the 19 children in a 4th grade class, 11 boys and 8 girls, from a suburban school participated in a one year health promotion project (IV). Data was collected through narratives in search for the children's lived experiences, by using open letters (I,II,III), drawings (IV), individual interviews (II,III), and group discussions (I,IV). The data was analyzed using a hermeneutic phenomenological data analysis (I,III,IV), and a phenomenological-hermeneutical data analysis (II). The findings of the four different studies included in this thesis can be summarized under the headings; Being met as a "we" - relationships to others and to oneself, Being caught in life's challenges, Being relaxed and powerful, and Friendship is like an extra parachute. The children's lived experiences point at the importance of being trusted, respected, included, involved and met as a "we". From this thesis it can be understood that including children in health promotion is a matter of openness and humbleness, suggesting adults, be it parents, health care ...